An experimental investigation of coupled chemico-mineralogical and mechanical changes in varyingly-cemented sandstones upon CO2 injection in deep saline aquifer environments. (15th August 2017) - Rathnaweera, T.D.; Ranjith, P.G.; Perera, M.S.A.; Ranathunga, A.S.; Wanniarachchi, W.A.M.; Yang, S.Q.; Lashin, A.; Al Arifi, N.
Abstract: Although CO2 storage in deep saline aquifers is now accepted as a potential option for atmospheric CO2 mitigation, the chemico-mineralogical property alterations in the aquifer formation associated with CO2 /brine/rock mineral interactions, the corresponding influence on formation hydro-mechanical properties and the effect of rock mineral structure, are not yet fully understood. This study was therefore conducted to obtain a comprehensive understanding of the effect of long-term CO2 exposure on the chemico-mineralogical structure and corresponding strength characteristics of saline aquifer rock formations using silicate cement (SS) and carbonate cement (CS) Hawkesbury sandstone samples collected from the Sydney basin. Sandstone samples were first reacted with brine+CO2 under different injection pressures (both sub-critical (4, 6 MPa) and super-critical (8, 10 MPa)) under a constant temperature of 35 °C. A comprehensive chemico-mineralogical analysis (ICP-AES and XRD) was first conducted on both the rock mass pore fluid and the rock matrix over the saturation period of one year, giving special attention to the alteration of dominant rock minerals (quartz, calcite and kaolinite). The overall influence after 12 months of saturation with brine and CO2 on the strength characteristics of the two types of sandstones (SS and CS) was then investigated and correlated with the chemico-mineralogical reaction, in order to understand the coupled process. According to the test results, compared to the silicate cement-dominant mineral structure (SS), the presence of a carbonate cement-dominant mineral structure (CS) in the aquifer rock formation creates more significant alterations in the formation's chemico-mineralogical structure upon CO2 injection. This is because calcite mineral reactions occur at much greater rates compared to quartz mineral reactions in CO2 -exposed environments. In addition, although some minor precipitation of kaolinite minerals may also occur upon CO2 injection, the effect may not be significant. Overall, rock mineral changes in deep saline aquifers upon CO2 injection have a significant influence on the strength characteristics of the reservoir rock mass, depending on the aquifer mineral structure, and CS formations are subject to much greater strength property changes upon exposure to CO2 than SS formations. Interestingly, CO2 injection causes a strength gain in SS sandstone and a strength reduction in CS sandstone. These mechanical property alterations in aquifer rock formations are also dependent on the CO2 injection pressure and phase, and increasing the injecting CO2 pressure significantly enhances the changes, due to the highly acidic environment created by the enhanced CO2 solubility process. Changing the CO2 phase from sub- to super-critical condition also accelerates the reaction mechanisms, due to the greater chemical potential of super-critical CO2 . However, overall SS sandstone exhibits more stable chemical-mineralogical and mechanical characteristics upon CO2 injection than CS sandstone, and exhibits more suitable characteristics for CO2 sequestration. Highlights: A series of chemical, mineralogical and strength tests were performed. Carbonate and silicate cemented reservoir conditions were selected. Dissolution of CO2 in aquifer pore fluid causes its mineral structure to be altered. Rock mineral alteration affects the mechanical behaviour of reservoir rock. Silicate cemented reservoirs exhibit more stable characteristics upon CO2 injection.